PENGEMBANGAN KIT PRAKTIKUM SAINS DARI BAHANDAUR ULANG DAN IMPLEMENTASINYA DALAM KEGIATANPPL-KKN MELALUI STRATEGI PEMBERDAYAANMASYARAKAT PEMULUNG TERDIDIK - Pujianto, Juli Astono, Budi Purwanta, (Universitas Negeri Yogyakarta, 2012)
The purpose of this public achievement is to develop the experimentkit from used materials that is the cooperation result of teachers, collegestudents, educated scavengers community and lecturers, and observe theability of Physics Education college students in using the experiment kitmade from used materials in the class lesson with cooperated teachers. andmake experiment modules to help students in understanding concepts ofusing the experiment kits in the cooperated schools.The targets of its acievement program is helping the 20-phisicsteachers, 30-college students of Physics Education and the educatedscavengers are 5 members to help experiment kits producing.The methods in this activity programs is a workshop by this time schedule, -8 hours talkative, - 32 hours for producing the experiment kits byscavengers community, and - 120 hours for school observation.The achieved results of this programs had been developedexperiment kits made from used materials, that is the results of cooperationof teachers, college students, educated scavengers and lecturers. And thePhysics Education college students ability in using the experiment kits inclass in fair. Besides that the experiment modules had been developed tohelp the students to understand the conceps related to the use directions ofexperiment kits in the cooperated schools.